1998
DOI: 10.1073/pnas.95.7.3925
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial attachment alters the outcome of Helicobacter pylori infection

Abstract: Genetically defined in vivo models are needed to assess the importance of target cell attachment in bacterial pathogenesis. Gastric colonization by Helicobacter pylori in human populations is common and persistent, and has various outcomes including peptic ulcers and cancer. The impact of attachment on the course of infection was examined in transgenic mice expressing a human receptor for H. pylori in their gastric epithelium. Persistent infection by a clinical isolate occurred at comparable microbial densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
168
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(177 citation statements)
references
References 37 publications
5
168
1
3
Order By: Relevance
“…Thus the presence of Le b in the host and BabA in the bacteria mediates adherence to the gastric epithelial lining and implies a supposedly more severe infection. Indeed, the ␣-1,3/4FT mice developed more severe gastritis when infected than their nontransgenic littermates and also develop autoantibodies against parietal cells (14). Gastric permeability was also increased in the infected mice, in conformity with findings in H. pylori-infected patients (11) and animals (34).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus the presence of Le b in the host and BabA in the bacteria mediates adherence to the gastric epithelial lining and implies a supposedly more severe infection. Indeed, the ␣-1,3/4FT mice developed more severe gastritis when infected than their nontransgenic littermates and also develop autoantibodies against parietal cells (14). Gastric permeability was also increased in the infected mice, in conformity with findings in H. pylori-infected patients (11) and animals (34).…”
Section: Discussionsupporting
confidence: 75%
“…␣-1,3/4FT mice use human ␣-1,3/4FT to express Le b epitopes in their pit region and surface mucus cells (14). Le b is a blood group antigen that is recognized by an H. pylori adhesin, blood group antigen-binding adhesin (BabA) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of a vaccine is the basic approach to H. pylori treatment, but efficacy data are still lacking in humans (Kusters, 2001). H. pylori is able to bind to several receptors at the surface of gastric epithelial cells (Guruge et al, 1998;Taylor et al, 1998); thus prevention of H. pylori binding to gastric epithelial cells could represent a potential target for H. pylori treatment. We previously reported that egg-yolk-derived immunoglobulin (IgY) obtained from hens that were immunized with H. pylori whole-cell lysate may provide a novel alternative approach to the treatment of H. pylori infection (Shin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These early observations, as well as the observation that GAG-like molecules and, possibly sulphated glycolipids bind to organisms grown in brain heart infusion broth encouraged a comparison of the influence of various media and culture conditions on expression of GAG binding. GAG-binding proteins of H. pylori were expressed optimally in GabCamp broth, unlike production of sialic acid-specific and other H. pylori HAS and Lewis-binding proteins which were expressed optimally on solid media such as GabCamp agar [50,51]. The opacity factor or Opa adhesin of N. gonorrhoeae was expressed when the bacteria were grown in polysaccharide-free medium [52].…”
Section: Glycosaminoglycan Binding In Microbial Adhesion To Mucosal Smentioning
confidence: 99%